Improving Observing Skills of High School Students through Guided Inquiry Model - Shafila Sahnaz; Harlita Harlita; Murni Ramli (International Journal of Pedagogy and Teacher Education, 2018)
Observation skill is one of the fundamental science process skills should mastered by students in the primary level. In fact, due to the lack of experiences of observation, high school students in the observed class showed the low level of observations skills. This study was three cycles-collaborative action research aims to improve the observation skills of high school students in biology through the implementation of guided inquiry learning integrated with a series of observation activities. The participants were 30 students of grade 11 of one public high school in Karanganyar, Indonesia. Six indicators of observation skills were used to assess the performance of students. In the pre-cycle stage, students showed relatively moderate performance on two aspects, e.g., identifying the differences and similarities of objects (45.83), and using of multiple senses to observe (45.83). But, they performed low in uses the apparatus correctly (4.17). On the skills of classifying the differences or the similarities, they scored 25, and for collecting relevant data they got 29.17 in average. After three iterative cycles, all indicators have increased significantly.